2021
DOI: 10.2174/1574893616666210203104013
|View full text |Cite
|
Sign up to set email alerts
|

Development of Machine Learning Based Blood-brain Barrier Permeability Prediction Models Using Physicochemical Properties, MACCS and Substructure Fingerprints

Abstract: Background: Blood-Brain Barrier (BBB) protects the central nervous system from the systemic circulation and maintains the homeostasis of the brain. BBB permeability is one of the essential characteristics of drugs acting on the central nervous system to indicate if the drug could reach the brain or not. The available laboratory methods for the prediction of BBB permeability are accurate but expensive and time-consuming. Therefore, many attempts have been made over the years to predict the BBB permeability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…SVMProt-188D is a feature extraction method based on the amino acid composition and physicochemical properties ( Dubchak et al, 1995 ; Saxena et al, 2021 ). It encodes each protein sequence as a 188-dimensional feature vector.…”
Section: Methodsmentioning
confidence: 99%
“…SVMProt-188D is a feature extraction method based on the amino acid composition and physicochemical properties ( Dubchak et al, 1995 ; Saxena et al, 2021 ). It encodes each protein sequence as a 188-dimensional feature vector.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, alternative methods with lower costs such as computational models are needed for drug development and research. Nowadays, due to the high-speed development of computational technology, various in silico prediction models to evaluate compound ADME properties have been developed, also for BBB transfer (shown in Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…Upon validation of the developed model using 1,566 compounds, the prediction accuracy was found to be 86.5% only. Very recently, Saxena et al (2021) proposed an ML-based BBB permeability prediction model using 1,978 compounds ( Saxena et al, 2021 ). The study group found that SVM with the RBF kernel yielded an accuracy of 96.77% with AUC and F1 score values of 0.964 and 0.975, respectively, which outperformed the kNN, random forest, and naïve Bayes algorithms in the prediction of BBB permeability on the same dataset.…”
Section: Introductionmentioning
confidence: 99%